Reference management training to improve the quality of scientific publications for vocational high school teachers - Rahayu Relawati; Bambang Yudi Ariadi; Gumoyo Mumpuni Ningsih (Universitas Muhammadiyah Magelang, 2024)
Recognizing the challenges faced by teachers in completing their portfolios due to limited knowledge and skills in writing scientific publications, this training program aimed to equip them with the necessary expertise in using Mendeley, a digital referencing tool, to enhance their scientific writing capabilities. The training was conducted online with 24 participants. The first day covered an introduction to Mendeley and citation practices, while the second day focused on hands-on Mendeley application. The training effectively enhanced participants' knowledge and skills in using Mendeley. Evaluation indicators revealed that none of the participants had installed the Mendeley application prior to the training, while 67% had installed it after the training. Furthermore, 54% of the participants were able to perform Mendeley practices both online and on desktops. Additionally, 73% of the participants expressed their intention to utilize Mendeley for action research, reference searching, and automated bibliography generation.